Drop jet in crossflow: ALE/Finite Element Simulations and interfacial effects. - Oliveira, Gustavo Charles Peixoto de (2015)
A two-phase flow computational code taking a hybrid Arbitrary Lagrangian-Eulerian desciption of movement along with the Finite Element Method is used to simulate the dynamics of an incompressible drop jet in crossflow in the primary breakup zone. Dispersed entities are described by means of a front-tracking method which produces zero-thickness interfaces through contiguous element meshing and adaptive refinement techniques. Periodic boundary conditions are implemented in a variationally consistent way for all the scalar fields involved in the presented simulations and amodified version of the pressure field is added to the one-fluid formulation employed in the momentum equation. Three-dimensional direct numerical simulations for different flow configurations of immiscible liquids pertinent to experimental results found in literature. Analyses of the hydrodynamics of the drop jet in crossflow in these configurations considering trajectories, drop shape variations, spectrum of small disturbances, besides additional aspects relating to mesh quality are presented and discussed.